The Al Jazeera’s visual stance on 30 June revolution: visual appraisal and intertextuality in dialogue - Fawzy Rania Magdi (Language and Semiotic Studies)
30 June Revolution and the military support that followed on 3rd of July are seen as controversial events that have led to redefining the key actors in the Egyptian authorities at that time: Muslim Brotherhood and the Egyptian Military. As new photos play an important role in promoting certain political aspects, the current study examines the Al Jazeera’s feature stories photos on this event. In doing so, the study synthesizes Appraisal theory with intertextuality and visual social actor representation. It takes from the issue of an intertextual view of evaluative stance as its point of departure. The concept of intertextuality is then related to the visual and hypertextual properties of online feature stories. The study finds that the photos depicting the military and security forces resort to certain visual techniques that emphasize the condemnation and criticism of such institutions. On the other hand, the Al Jazeera online visually evaluates the Brotherhood Group and the supporters of Morsi positively.